Evaluation of fuel consumption, pollutant emissions and well-to-wheel GHGs assessment from a vehicle operation fueled with bioethanol, gasoline and hydrogen. (15th October 2020) - Jhang, Syu-Ruei; Lin, Yuan-Chung; Chen, Kang-Shin; Lin, Sheng-Lun; Batterman, Stuart
Abstract: With the depletion of oil and natural reserves, gasoline-bioethanol blend has been considered as one of the finest alternative fuels. However, the fuel blend can also lead to higher fuel consumption as a result of adverse influence. Hydrogen as fuel additive contains many benefits in comparison to other petroleum since it promotes oxidation and decreases pollutant compounds during the combustion process. Therefore, this study aims to investigate the effect of pollutant emissions, fuel consumption and well-to-wheel GHG emissions from a vehicle operating with gasoline-bioethanol blend (E3, E6 and E10), and hydrogen produced (0.6 LPM) on-board under cold start and FTP-75 transient cycle. The results show that hydrogen addition fueled with gasoline-bioethanol blend (E6 and E10) improves diffusion speed and homogeneous mixing, benefiting the complete combustion of fuel-air mixture. The significant reduction of CO, HC and NOx could be found under cold start and FTP-75. The reduction of 0.096, 1.19 and 1.10% on fuel consumption were obtained for E3, E6 and E10 with hydrogen addition. From the environmental point of view, the E10 with and without hydrogen addition appears to be agreeable since the outcome of well-to-wheel GHG emissions account for significant reduction in comparison with the base fuel (G0). Highlights: The effect of cold start and full cycle by FTP-75 condition were studied. Hydrogen addition with E6, E10 reduced accumulated emission mass in cold start. Vehicle fuel consumption was reduced by hydrogen addition. Well-to-tank accounts for 22.3% of the well-to-wheel greenhouse gas emissions. Compared to conventional gasoline, greenhouse gas was found reduced by 6.95% in E10.